PENERAPAN MODEL AKTIVE LEARNING DENGAN METODE CROSSWORD PUZZLE DALAM PEMBELAJARAN EKONOMI KELAS X PADA SMAN 10 PONTIANAK - Susiana, Elis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this study is to determine the effectiveness of the implementation of Active Learning model with Crossword Puzzle method in the learning of class X economics at SMAN 10 Pontianak. The method used in this research is the experimental method with the experimental quasi-experimental design with the design of time series research design. The subjects in this study are students of class XE SMAN 10 Pontianak with 39 students. Data collection techniques used are direct observation techniques, direct communication techniques, measurement techniques, documenter study techniques. The data collection tools used are test, observation sheet, note sheet. The result of the research is 4 times The meeting with each 4 times pre-test and post-test, there is difference before the implementation of active learning model with crossword puzzle method with the first meeting of student grade increase is 12,5, second meeting 10,52, meeting Third 14.34, fourth meeting 18.82. And Ho is rejected because its value <0,05 (see significance 0,000) with Ha intention is accepted, it can be concluded that in this test there is effectiveness of learning outcomes after applying the active model of learning by crossword puzzle method in the learning of class x economy at SMA Negeri 10 Pontianak. Keywords: Crossword Puzzle Method, Learning Result, Economic Learning